Continued Low Rates of Hepatitis C Virus (HCV) Recurrence in HCV/HIV- and HCV-Infected Participants Who Achieved Sustained Virologic Response After Direct-Acting Antiviral Treatment: Final Results From the AIDS Clinical Trials Group A5320 Viral Hepatitis C Infection Long-term Cohort Study (V-HICS). (14th October 2021) - Wyles, David L; Kang, Minhee; Matining, Roy M; Murphy, Robert L; Peters, Marion G
Abstract: Final results from the long-term Viral Hepatitis C Infection Long-term Cohort Study (V-HICS) found low rates of hepatitis C virus (HCV) recurrence after direct-acting antiviral therapy in both HCV/human immunodeficiency virus (HIV)–coinfected (0.67/100 person-years) and HCV-infected (0.2/100 person-years) groups with >500 person-years of follow-up. Confirmed reinfections were in participants with HIV who reported high-risk behaviors.